The Internationalisation Decision of Nigerian Firms - Ugwu, Uchechukwu C. (2020)
African multinationals are on the rise, they have emerged as strong (regional) players in various sectors of the economy. However, the internationalisation of African firms has received relatively less attention in research on emerging market enterprises, many studies focus primarily on Asian and Latin American firms. This study aims to address this gap in the literature and draws upon conventional and emerging theories of Foreign Direct Investment (FDI) and Dunning’s seeking motives to examine the factors that drive the outward FDI decisions of African firms. Using a qualitative, case-study approach, this study explores the case of four Nigerian firms (three from the banking industry and one from the cement industry) using secondary data and highlights what factors have contributed to their international expansion. The research findings illustrate how outward FDI decisions are shaped by firm-specific factors, the institutional environment resulting from home country-specific factors and firms’ FDI motives, these internal and external factors can either encourage or discourage firms from operating outside their domestic market. This research has important theoretical and practical implications; it advances understanding of internationalisation from an African perspective and provides guidance for Nigerian firms seeking to expand abroad.